2021
DOI: 10.15252/embj.2020105026
|View full text |Cite
|
Sign up to set email alerts
|

C9orf72 ALS/FTD dipeptide repeat protein levels are reduced by small molecules that inhibit PKA or enhance protein degradation

Abstract: Intronic GGGGCC (G4C2) hexanucleotide repeat expansion within the human C9orf72 gene represents the most common cause of familial forms of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) (C9ALS/FTD). Repeat-associated non-AUG (RAN) translation of repeat-containing C9orf72 RNA results in the production of neurotoxic dipeptide-repeat proteins (DPRs). Here, we developed a high-throughput drug screen for the identification of positive and negative modulators of DPR levels. We found that HSP90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 109 publications
0
11
0
Order By: Relevance
“…Therefore, we used SNORD118 -mutant human iPSC-derived NPCs and performed cell-based small-molecule screen for reversing proliferation defects in mutant NPCs. On the basis of published studies, we selected those chemical compounds that potentially affect ribosome biogenesis and nucleoli functions, including 2BAct ( 38 ), MCL-186 ( 39 ), bromosporine ( 40 ), nicotinamide ( 41 ), tideglusib ( 42 , 43 ), PFI-1 ( 44 ), YM201636 ( 45 ), cilostazol ( 46 ), leucine ( 47 ), and prostetin ( 48 ). Our initial EdU assay–based cell proliferation screen identified 2BAct, MCL-186, and cilostazol, which significantly increased the proliferation of SNORD118 *5C>G -mutant NPCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we used SNORD118 -mutant human iPSC-derived NPCs and performed cell-based small-molecule screen for reversing proliferation defects in mutant NPCs. On the basis of published studies, we selected those chemical compounds that potentially affect ribosome biogenesis and nucleoli functions, including 2BAct ( 38 ), MCL-186 ( 39 ), bromosporine ( 40 ), nicotinamide ( 41 ), tideglusib ( 42 , 43 ), PFI-1 ( 44 ), YM201636 ( 45 ), cilostazol ( 46 ), leucine ( 47 ), and prostetin ( 48 ). Our initial EdU assay–based cell proliferation screen identified 2BAct, MCL-186, and cilostazol, which significantly increased the proliferation of SNORD118 *5C>G -mutant NPCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been shown that DPR proteins inhibit the UPS in cell culture. ,, Additional work has shown that increasing protein degradation through the use of a DUB inhibitor, HSP90 inhibitor, or activation of the proteasome through cAMP/protein kinase A-dependent phosphorylation of proteasome subunit PSMD11 counters the toxic effects of the DPR proteins. This suggests that impairment of UPS function contributes to DPR protein toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in C. elegans model, loss‐of‐function of eukaryotic translation initiation factor 2D decreased poly‐GA and poly‐GR expression level (Sonobe et al, 2021) (Figure 3). Protein kinase A(PKA) enhances poly‐GP expression, and inhibition of PKA by its inhibitor H89 reduces poly‐GP levels in iPSC‐derived motor neurons (Licata et al, 2022). As above, multiple layers of regulations could underlie C9 RAN translation; however, complete picture of C9 RAN translation is yet clear.…”
Section: Initiation and Modulation Of Ran Translationmentioning
confidence: 99%